Nguyễn Đình Chiểu’s worldview: Content and historical significance - Ngoc, Lai Quang (The International tax journal, 2024)
This study focuses on analyzing Nguyễn Đình Chiểu’s worldview, highlighting core values such as righteousness, filial piety, patriotism, and compassion for the people. These principles deeply reflect the national spirit, ethics, and social responsibility of the Vietnamese people during the era of foreign invasion. His thought not only inspired resistance, unity, and determination during the anti-French struggles of the 19th century but also shaped the values for future generations. The historical significance of Nguyễn Đình Chiểu’s ideas transcends time, becoming a treasured cultural and ethical legacy of the Vietnamese nation.